2009
DOI: 10.1155/2009/821013
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Mycophenolat Mofetil of Steroid-Dependent Asthma—One Case of Severe Asthma

Abstract: Background. Some patients with severe nonallergic asthma can be difficult to treat with conventional therapy. Mycophenolat Mofetil (MMF) is an immunosuppressive drug with multiple mechanisms. There is theoretical support of specific effect of MMF on severe asthma, in “difficult to treat” patients. The aim of the present case was to explore whether MMF had an effect in one case of severe refractory asthma. The patient. This case deals with one patient with very severe nonallergic treatment refractory asthma who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The application of MMF for patients with severe therapy-resistant asthma was described in a case study of 22 patients in which more than half of the patients benefitted from the treatment [126]. In an earlier study, the successful treatment of a patient suffering from non-allergic, therapy-resistant asthma with MMF had been reported [127]. Also, for severe cases of atopic dermatitis, which were not adequately controlled by topical treatment, MMF was successfully applied [128].…”
Section: Mycophenolate Mofetil-mycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…The application of MMF for patients with severe therapy-resistant asthma was described in a case study of 22 patients in which more than half of the patients benefitted from the treatment [126]. In an earlier study, the successful treatment of a patient suffering from non-allergic, therapy-resistant asthma with MMF had been reported [127]. Also, for severe cases of atopic dermatitis, which were not adequately controlled by topical treatment, MMF was successfully applied [128].…”
Section: Mycophenolate Mofetil-mycophenolate Mofetil (Mmf)mentioning
confidence: 99%
“…16 To emphasize this relationship, the KEGG pathway has05310 (asthma) is significantly enriched directly in genes of the MMF molecular footprint. So far MMF has not been commonly considered in inflammatory respiratory diseases although recently its beneficial role and future clinical studies have been suggested based on success in a patient with treatment resistant severe non-allergic asthma, 43 an effect probably based on reduced bone marrow eosinophilopoiesis. 44 The next group of drugs is constituted by a number of Ca + + transporting ATPase (ATP2C1) targeting, inhaled anesthetics including isoflurane, desflurane, methoxyflurane, enflurane and sevoflurane.…”
Section: Drug Targets Linked To Mmf In Explicit Synthetic Lethal Inte...mentioning
confidence: 99%
“…This represents the largest case series of MMF in treatment-resistant asthma. There has only been one previous single case report [4] and a report of beneficial experience in a Churg-Strauss-like syndrome [5].…”
mentioning
confidence: 99%
“…Total IgE was 2048 kU?L -1 , white blood cell count 7.81610 9 L -1 and eosinophil count was raised at 0.75610 9 L -1 . Two-hourly peak flow measurements made at home and work over 4 weeks were analysed using OASYS [3,4]. The OASYS score was 3.4 and the area between the curves score was 23.4 L?min -1 ?h -1 confirming a significant work effect ( fig.…”
mentioning
confidence: 99%